2014
DOI: 10.1002/2014jg002709
|View full text |Cite
|
Sign up to set email alerts
|

Improving ecosystem productivity modeling through spatially explicit estimation of optimal light use efficiency

Abstract: A common assumption of remote sensing-based light use efficiency (LUE) models for estimating vegetation gross primary productivity (GPP) is that plants in a biome matrix operate at their photosynthetic capacity under optimal climatic conditions. A prescribed constant biome maximum light use efficiency parameter (LUE max ) defines the maximum photosynthetic carbon conversion rate under these conditions and is a large source of model uncertainty. Here we used tower eddy covariance measurement-based carbon (CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 123 publications
3
67
0
Order By: Relevance
“…In this study, the optimized values were 1.839 g C MJ −1 , 1.831 g C MJ −1 , and 0.672 g C MJ −1 for forests, crops, and grass, respectively, which were in the range of 0.796–2.53 g C MJ −1 , 1.056–3.864 g C MJ −1 , and 0.199–1.8818 g C MJ −1 for forests, cropland, and grassland, respectively [ J. Chen et al ., ; Zhang et al ., ]. However, ɛ max was found to be spatially heterogeneous within biome types [ B. Chen et al ., ; Madani et al ., ]. But the observed GPP in cropland was available only from one site in this study and the optimized parameter was applied to regional scale, which would be the main reason of the overestimated NPP.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the optimized values were 1.839 g C MJ −1 , 1.831 g C MJ −1 , and 0.672 g C MJ −1 for forests, crops, and grass, respectively, which were in the range of 0.796–2.53 g C MJ −1 , 1.056–3.864 g C MJ −1 , and 0.199–1.8818 g C MJ −1 for forests, cropland, and grassland, respectively [ J. Chen et al ., ; Zhang et al ., ]. However, ɛ max was found to be spatially heterogeneous within biome types [ B. Chen et al ., ; Madani et al ., ]. But the observed GPP in cropland was available only from one site in this study and the optimized parameter was applied to regional scale, which would be the main reason of the overestimated NPP.…”
Section: Discussionmentioning
confidence: 99%
“…This LUE‐based GPP approach provides the foundation of the current MODIS GPP product (Running et al ., ). Increasing numbers of eddy‐covariance flux towers have provided valuable information to calibrate this LUE‐based GPP model, particularly the value of LUE GPP and how it varies under environmental stresses (Turner et al ., ; Hilker et al ., ; Coops et al ., ; Madani et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…These changes, integrated across leaves within a forest canopy, would likely result in different post-disturbance biotic and Table 1. abiotic dynamics; FASET has already shown the assumption of a fixed LUE not to be true at the stand level . Recent work has also shown that the use of a spatially variable LUE parameterization, using C flux measurements from the Fluxnet data set, can significantly improve the accuracy of modeled GPP (Madani et al, 2014). Maintenance of canopy light absorption in the FASET forest depends on a structurally heterogeneous canopy so that subdominant trees quickly increase their absorption following the girdling of canopy dominants .…”
Section: Model Mechanisms and Behaviorsmentioning
confidence: 99%